Analyzing e-Service Quality and e-Satisfaction Effects on Customer Loyalty at An Indonesian Digital Marketplace - Koko Wahyu Prasetyo; Rizky Putra Pratamal; Addin Aditya (Universitas Medan Area, 2022)
Indonesia is listed as one of the countries with the most population in the world as well as one of the countries with the most internet users. With this fact, Indonesia is one of the largest potential markets in the digital trade sector. Many Indonesian people use the internet and marketplace platforms to shop and fulfill their daily needs. Indonesia is also the base of operations for several marketplace platforms with significant transaction values, one of which is Tokopedia. Tokopedia is one of the Indonesian marketplace platforms that consistently ranks in the top 3 for the category of online buying and selling sites that people are interested in. Some studies have stated that the quality of business services affects customer satisfaction and loyalty. This quality is one of the indicators that determine customer satisfaction with the company's products and services. This study analyzes the influence of the dimensions of electronic service quality and the aspects of customer satisfaction on customer loyalty in the Tokopedia marketplace. It analyzes the effect of the dimensions in the ES-Qual model on overall ES-Qual, e-satisfaction, and e-loyalty on consumers. The data obtained were analyzed using the variant-based Partial Least Square Structural Equation Model (PLS-SEM) equation model which can simultaneously test the measurement model, as well as the structural model. The results also show that online service quality and overall service quality affect online user satisfaction and online user loyalty.